2019
DOI: 10.1002/ijgo.12837
|View full text |Cite
|
Sign up to set email alerts
|

A district‐wide population‐based descriptive study of emergency peripartum hysterectomy in a middle‐income country

Abstract: Objective To determine incidence, risk indicators, and outcomes of emergency peripartum hysterectomy (EPH) in Metro East, Cape Town, South Africa. Methods A population‐based district‐wide prospective descriptive study of EPH in public hospitals from November 2014 to November 2015. Women were enrolled by using the WHO maternal near miss tool and followed until discharge. EPH was defined as hemorrhage or infection leading to hysterectomy during pregnancy or within 42 days of delivery. Results Fifty‐nine women ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…For the African continent, according to 17 epidemiological studies, the annual incidence of hemostasis hysterectomies among all deliveries ranged from 0.12% in South Africa to 1.25% in Niger [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the African continent, according to 17 epidemiological studies, the annual incidence of hemostasis hysterectomies among all deliveries ranged from 0.12% in South Africa to 1.25% in Niger [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fatality rate of emergency peripartum hysterectomy is the highest in low-resource settings. 4 In its criteria for assessing maternal health quality of care, the WHO includes the performance of emergency peripartum hysterectomy secondary to infection as a "maternal near-miss" -an event in which a woman "nearly died but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy." 3,5 While the mortality associated with puerperal sepsis in sub-Saharan Africa is significant and exceeds that in high resource settings, we lack an accurate estimate of its true incidence and impact.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Recent studies in South Africa found that puerperal sepsis was a primary indication for emergency peripartum hysterectomy in up to 46% of cases. 4 , 9 , 10 A standard protocol guiding emergency peripartum hysterectomy secondary to puerperal sepsis remains unclear and there is a scarcity of recent literature regarding clinical course and outcomes in settings with limited access to antibiotics. As a result, the incidence of emergency peripartum hysterectomy is greatly influenced by clinical impression and factors such as delayed recognition of puerperal sepsis, availability of adequate antibiotics, and delays in transfer to specialist care at the tertiary center.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations